Molecular Mechanisms and Epidemiology of Fosfomycin Resistance in Staphylococcus aureus Isolated From Patients at a Teaching Hospital in China - Xu, Wenya; Chen, Tao; Wang, Huihui; Zeng, Weiliang; Wu, Qing; Yu, Kaihang; Xu, Ye; Zhang, Xiucai; Zhou, Tieli (Frontiers in Microbiology, 2020)
Staphylococcus aureus is a major cause of hospital- and community-acquired infections rendering a significant burden on the healthcare system. With the widespread of multi-drug-resistant bacteria and the lack of effective antibacterial drugs, fosfomycin has gradually attracted attention as an “old drug”. Thus, the resistance mechanisms and epidemiology of fosfomycin-resistant S. aureus is an urgent requirement. In order to investigate the mechanisms of resistance, 11 fosfomycin-resistant S. aureus isolates were analyzed by PCR and sequencing. The genes, including fosA, fosB, fosC, fosD, fosX, and tet38, as well as mutations in murA, glpT, and uhpT were identified. Quantitative real-time PCR (qRT-PCR) was conducted to evaluate the expression of the target enzyme gene murA and the efflux pump gene tet38 under the selection pressure of fosfomycin. Furthermore, multilocus sequence typing (MLST) identified a novel sequence type (ST 5708) of S. aureus strains. However, none of the resistant strains carried fosA, fosB, fosC, fosD, and fosX genes in the current study, and 12 distinct mutations were detected in the uhpT (3), glpT (4), and murA (5) genes. qRT-PCR revealed elevated expression of tet38 gene when exposed to increasing concentration of fosfomycin among 8 fosfomycin-resistant S. aureus strains and reference strain ATCC 29213. MLST analysis categorized the 11 strains into 9 STs. Thus, the mutations in the uhpT, glpT, and murA genes might be the primary mechanisms underlying fosfomycin resistance, and the overexpression of efflux pump gene tet38 may play a major role in the fosfomycin resistance in these isolates.